LO91: Repeat exposures to culprit drugs contribute to adverse drug events in emergency department patients. (15th May 2017) - Hohl, C.M.; Woo, S.; Cragg, A.; Villanyi, D.; Wickham, M.E.; Ackerley, C.R.; Scheuermeyer, F.X.
Abstract : Introduction: Adverse drug events (ADEs), unintended and harmful events associated with medications, cause or contribute to 2 million annual emergency department (ED) visits in Canada. Australian data indicate that 27% of ADEs requiring admission are events caused by re-exposure to drugs that previously caused harm. Ourobjective was to estimate the frequency of repeat ADEs.Methods: We reviewed the charts of ADE patients who had been enrolled in 1 of 3 prospective studies conducted in 2 tertiary care and 1 urban community ED. In the parent studies, researchers enrolled patients by applying a systematic selection algorithm to minimize selection bias, and physicians and pharmacists evaluated patients prospectively to evaluate the causal association between the drug regimens and patient presentations. After completion of the parent studies, a research pharmacist and a physician independently reviewed the charts of ADE patients, abstracted data using electronic forms, and searched that hospital's records for previously recorded ADEs. The main outcome was a repeat ADE, defined as a same or same-class drug re-exposure, or repeat inappropriate drug withdrawal, causing a same or similar presentation as a prior ADE. Sample size was based on enrolment into the parent studies.Results: We reviewed the charts of 614 ED patients diagnosed with 655 ADEs. Of these, 20% (133/665, 95%CI 17.0-23.0%) were repeat events. Most repeat ADEs were moderate (61%) or severe (32%) in nature, and 33% (95%CI 25.1-41.1%) required hospital admission. The most commonly implicated drugs were warfarin (10%), hydrochlorothiazide (4%) and insulin (4%), and the most commonly implicated drug classes were antithrombotics (17%), psychotropics (12%) and analgesics (9%). Repeat ADEs commonly required clinical monitoring (59%), additional medications to treat the ADE (50%) and follow-up lab testing (35%). Overall, 61% (95%CI 51.3-70.7%) of culprit drug re-exposures were deemed potentially or definitely inappropriate.Conclusion: Inappropriate re-exposures to previously harmful medications cause a substantial number of recurrent ADEs, and may represent an ideal target for prevention. We were unable to search for repeat ADEs in the records of other hospitals that our patients may have visited, and could not detect ADEs that were not documented in the medical record. As a result, we likely underestimated the frequency of repeat ADEs.